Unilateral Transverse Sinus Stenting of Patients with Idiopathic Intracranial Hypertension - Bussière, M. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: The pathophysiology of IIH remains unknown. TS stenoses have been observed in a high proportion of these patients. Stent placement to remove this potential obstruction to venous outflow has been proposed as a treatment option for patients with IIH refractory to medical treatment. MATERIALS AND METHODS: The clinical presentation, treatment, and outcome of patients with refractory IIH evaluated for venous sinus stent placement at a tertiary care center was retrospectively reviewed. RESULTS: Thirteen female patients with IIH were evaluated for sinovenous stent placement. Moderate sinus stenoses with normal intrasinus pressures were found in 3 patients and therefore stent placement was not performed. Ten patients had elevated intrasinus pressures (pressure gradient across stenosis, 11–50 mm Hg), which decreased following unilateral TS stent placement. Headaches improved or resolved in all stented patients. Papilledema resolved completely or almost completely in 8 patients and significantly improved in 2 patients. One patient developed optic atrophy. There were no major periprocedural complications. CONCLUSIONS: In this small case series, restoring the patency of stenotic venous sinuses with a stent in patients with refractory IIH resulted in symptomatic improvement in all treated patients. The safety and efficacy of this procedure should be evaluated in a randomized controlled study to determine its role within the armamentarium of therapeutic options for patients with IIH.